Intention to use Paylater in Indonesia based on the technology acceptance model analysis - Febrisa Putri Deswari; Dina Patrisia (Operations Management and Information System Studies, 2022)
This study aims to determine (1) The effect of perceived security on perceived ease of use. (2) The effect of perceived ease of use on intention to use. (3) The effect of perceived security on intention to use through perceived ease of use as a mediating variable. (4) The influence of perceived security on perceived usefulness. (5) The effect of perceived usefulness on intention to use. (6) The effect of perceived security on intention to use through perceived usefulness as a mediating variable. (7) Effect of perceived ease of use on perceived usefulness. (8) The effect of social influence on intention to use. (9) The effect of social influence on perceived usefulness. The population in this study are people who have never used Paylater. The number of samples in this study were 210 respondents. The data in this study were collected through online questionnaires and data processing was carried out using Structural Equation Modeling (SEM) and using SmartPLS software. The results of this study indicate that all hypotheses are accepted.